PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY TERHADAP MINAT MEMBACA SISWA SEKOLAH DASAR - Muhamad Sudharsono; Angghi Apryani; Devi Irviani Wulandari; Bella Isnaeni; Nani Assyifa Putri; Alvina Damayanti (STKIP Subang, 2024)
This research describes the efficacy of Augmented Reality (AR) as a teaching aid to improve elementary school students' reading skills, particularly in letter recognition. Based on statistics showing that Indonesian children's reading skills are below the world average, this research highlights the importance of early reading skill development and the implementation of student-friendly teaching strategies. Through a qualitative examination of AR-based resources that had been approved by media, language, and content experts, this study sought to close the gap between students' digital interests and their reading development needs. As a result, the AR materials were highly effective; media experts rated them highly valid, language experts rated them valid, and content experts rated them highly valid. This suggests that augmented reality (AR) can offer an engaging and fun educational experience that can improve students' reading proficiency and motivation alongside their academic performance. The study also highlights the need for educational programs that integrate conventional and digital approaches, as well as the role of parents in encouraging their children's reading habits. It is suggested that technology be incorporated into the classroom to provide an effective and engaging learning environment for today's students. According to this study, AR has a lot of potential for literacy education, offering new opportunities to improve teaching methods and foster reading interest in young communities. Further research is recommended to investigate the longevity of the impact and use of AR in various educational contexts